Economic Growth Behind the Board Post Pandemic (Literature Study Analysis) - Abdulloh, Abdulloh (Journal of World Science, 2022)
Introduction: Population growth in Indonesia is getting higher. This change is influenced by population density. Economic growth in the behind-the-board area is still volatile; this can be addressed by planning for human resource development and managing business fields in several regional sectors. The purpose of this study is to analyze the economy of Balikpapan in 2022. Method: This study uses a qualitative literature study method. Through data collection from journals and other literature supporting media. Result: The study results indicate that the economy behind the board area needs to develop a strategy to adjust the existing potential by increasing the balance of human resources as management staff. It is based on the performance achievements of local companies by collaborating in the international market sector. The achievement of business economic development through increasing MSMEs in several areas behind the board is an effort to improve the creative economy. Conclusion: The market shift has created a new attribute among the business, tourism and micro and macroeconomic sectors. The development aspect supports regional progress in economic growth with the high capacity of the population in Indonesia, especially behind the board. The creative economy has become a significant change from the existence of the Indonesian youth creative economy movement.